The Presence of Memory Through Materiality, Spatial Configuration, and Collective as A System For Sustainable High-Rise Residence - Harani, Arnis Rochma; Mekarwangi, Brigitta E.; Hasan, Muhamad I. (UI Scholars Hub, 2023)
This paper aims to explore the multifaceted elements involved in the design of residential buildings, encompassing both landed and high-rise structures, with a particular focus on memory. The ever-increasing urban population density has prompted a shift towards high-rise living, leading many individuals to transition from traditional landed homes. However, in urban environments where closely-knit communities have been the norm, high-rise living is often perceived as a potential obstacle to fostering social interactions akin to those experienced in landed residential areas. This challenge presents a compelling opportunity for designers to create vertical residential spaces that maintain the vibrant communal ambiance found in traditional neighborhoods. To address this challenge, the concept of interiority comes to the forefront, emphasizing the intricate interplay between individuals and their living environments. This paper adopts a design-based exploration methodology, drawing insights from various facets of interiority and integrating them into the design process. Through this exploration, the study underscores the pivotal role of memory in establishing a social ambiance during the transition from low-rise to high-rise living. The manifestation of memory is elucidated through three key dimensions: Spatial arrangements, cultural influences, and the thoughtful consideration of collective activities. These dimensions collectively form a comprehensive framework for developing high-rise residential structures that prioritize and enhance the social bonds among their residents.